Teacher’s identification of students with reading difficulties in the upper grades of elementary school - Lipec Stopar, Mojca; Jenko, Nika (Specijalna edukacija i rehabilitacija, 2026)
Introduction. Teachers play a key role in detecting students with reading difficulties, yet identifying older elementary students who mainly read silently remains challenging. Traditional fluency assessments focus on oral reading and do not fully capture reading efficiency—the integration of fluent, automatic decoding and real-time comprehension. This study develops and provides initial validity evidence for the Speed Reading Test (SRT), a silent-reading measure of reading efficiency, and examines its links to comprehension and academic outcomes. Aim. To provide initial validity evidence for the SRT as a silent-reading measure of reading efficiency and examine its associations with teacher-rated reading ability, language background, prior additional professional support (APS), and grades in key subjects. Methods. The sample comprised 1.315 students (653 fifth- and 662 eighth-graders) from 17 Slovenian primary schools. Data included gender, first language, APS history, teacher-rated reading, and final grades. The 25-item timed SRT was administered alongside reading comprehension, vocabulary, and syntax tests. Independent-samples t-tests and Pearson correlations examined subgroup differences and associations with achievement. SRT cut-offs were determined by comparison with comprehension scores. Results. Girls outperformed boys, with the gap widening by Grade 8. Students from non-Slovene-speaking homes and those with APS scored significantly lower on the SRT. The SRT correlated strongly with teacher-rated reading (r ≈ .63) and moderately with school grades (r = .45–.57, p < .01). A 20th-percentile cut-off helped identify students at potential risk of poor comprehension. Conclusions. The SRT is a practical classroom tool for identifying upper-grade students whose silent-reading difficulties hinder achievement. Combined with teacher observations, it supports timely, data-informed instruction and progress monitoring.